Tether Anchors in Pickup Trucks: Assessing Usability, Labeling and Performance - Klinich, Kathleen D; Manary, Miriam A; Malik, Laura A; Flannagan, Carol (University of Michigan, Ann Arbor, Transportation Research Institute, 2016)
Technical Report Final This project investigated factors relating to tether use and misuse in pickup trucks and evaluated four interventions designed to educate consumers on proper use. The dynamic performance of four tether locations was also evaluated. Volunteer testing was performed with 24 subjects on 4 different pickup trucks using 2 forward-facing child restraints (Britax Marathon G4.1 and the Evenflo Triumph), with each subject performing 8 child restraint installations on the set of four vehicles. Pickup trucks were selected to represent four different implementations of tether anchors in pickup trucks: Chevy Silverado (plastic wire loop routers), Dodge Ram (webbing routers), Nissan Frontier (back wall anchor), and Toyota Tundra (webbing routers plus metal anchor). Interventions included a diagram label, QR code linked to video instruction, coordinating (i.e., low contrast with interior trim) text label, and contrasting-color text tag. Subjects used the tether in 93% of trials. However, tether use was completely correct in only 9% of trials. The installation was considered functional if the subject attached the tether to a tether anchor and had a tight installation (ignoring routing and head restraint position); 28% of subjects achieved a functional installation. The most common error was attaching the tether anchor to the anchor/router directly behind the child restraint rather than placing it through the router and attaching it to the anchor in the adjacent seating position. The Nissan Frontier, with the anchor located behind the seatback, had the highest rate of correct installations but also had the highest rate of attaching to components other than a tether anchor (seat adjustor, child restraint hardware, head restraint). None of the interventions had a significant effect on correct installation; not a single subject scanned the QR code to access the video instructions. The most successful subjects spent extensive time reviewing the vehicle manuals. Results indicate that current implementations of ...